2023
DOI: 10.3390/diagnostics13050976
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Fibrinogen as a Predictor of Perioperative-Blood-Component Transfusion in Major-Nontraumatic-Orthopedic-Surgery Patients: A Cohort Study

Abstract: There is a trend towards increased perioperative bleeding in patients with plasma fibrinogen levels < 200 mg/dL−1. This study aimed to assess whether there is an association between preoperative fibrinogen levels and perioperative blood-product transfusion up to 48 h after major orthopedic surgery. This cohort study included 195 patients who underwent primary or revision hip arthroplasty for nontraumatic etiologies. Plasma fibrinogen, blood count, coagulation tests, and platelet count were measured preopera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Several studies have reported various blood transfusion‐related risk factors such as artificial heart valve presence, 11 anesthesia choice, 12 and maximum clot firmness (FIBTEM), 61 which were not included in our prediction model. Although fibrinogen, 10 free fatty acids 13 and other factors were considered, the small sample size prevented us from establishing a correlation with blood transfusion. We anticipate that with a larger database, future studies will identify and incorporate more factors affecting postoperative blood transfusion, such as the patient's primary disease, anesthesia type, surgical approach, degree of injury, and blood coagulation hardness, thereby enhancing the model's predictive accuracy.…”
Section: Limitations and Future Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have reported various blood transfusion‐related risk factors such as artificial heart valve presence, 11 anesthesia choice, 12 and maximum clot firmness (FIBTEM), 61 which were not included in our prediction model. Although fibrinogen, 10 free fatty acids 13 and other factors were considered, the small sample size prevented us from establishing a correlation with blood transfusion. We anticipate that with a larger database, future studies will identify and incorporate more factors affecting postoperative blood transfusion, such as the patient's primary disease, anesthesia type, surgical approach, degree of injury, and blood coagulation hardness, thereby enhancing the model's predictive accuracy.…”
Section: Limitations and Future Developmentmentioning
confidence: 99%
“…Numerous studies have analyzed the risk factors associated with blood transfusion after total hip surgery, 9 , 10 , 11 , 12 , 13 , 14 including patient baseline information, surgical details, and preoperative test indicators. However, few studies have integrated these data to assess their relative importance in determining postoperative blood transfusion risk.…”
Section: Introductionmentioning
confidence: 99%